Eksplorasi Potensi Bioaktif Chingkui sebagai Nutraseutikal: Integrasi Etnofarmakologi dan Analisis Nutrigenomik - Ardhana Yulisma; Husniyah, Husniyah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Chingkui, a traditional dish from Lamno, Aceh, is prepared using glutinous rice and coconut, two natural ingredients that are recognized for their substantial health benefits. In addition to providing stable energy, both ingredients support heart health, digestion, and enhance the immune system. Given the mounting interest in functional foods, variations of chingkui that incorporate herbal ingredients such as pandan leaves, turmeric, black pepper, and mangkokan leaves offer additional health benefits, including anti-inflammatory, anti-diabetic, and antihypertensive effects. The present article aims to explore the nutritional content and health benefits of chingkui, as well as its potential development as a functional food. Chingkui has the potential to serve as a viable health food option, offering a distinctive flavor profile while concurrently promoting a nutritionally balanced diet that aligns with the contemporary nutritional requirements of the population.